2000
DOI: 10.1080/07315724.2000.10718943
|View full text |Cite
|
Sign up to set email alerts
|

Free Amino Acid Content in Standard Infant Formulas: Comparison with Human Milk

Abstract: Breastfed infants are supplied with FAA, mainly glutamic acid and glutamine, compared to formula-fed counterparts. The different FAA intake might be the origin of some functional differences at the enteral level between breast- and formula-fed infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
100
3
12

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(123 citation statements)
references
References 21 publications
8
100
3
12
Order By: Relevance
“…While glutamic acid and taurine are the two most abundant FAAs in human milk, accounting for more than 55% of total FAA, free taurine alone accounts for half the FAA in infant formula, and glutamic acid is third on the list. Similar results have been found by others (Agostoni et al, 2000;Ferreira, 2003). It has been suggested that these differences in glutamic acid, glutamine, and taurine may contribute to differences in enteral mucosa protection, neurotransmitters, and nitrogen supply in infant-fed infants (Windmueller, 1982;Chesney et al, 1998;Agostoni et al, 2000).…”
Section: Essential Vs Nonessential Amino Acidssupporting
confidence: 77%
“…While glutamic acid and taurine are the two most abundant FAAs in human milk, accounting for more than 55% of total FAA, free taurine alone accounts for half the FAA in infant formula, and glutamic acid is third on the list. Similar results have been found by others (Agostoni et al, 2000;Ferreira, 2003). It has been suggested that these differences in glutamic acid, glutamine, and taurine may contribute to differences in enteral mucosa protection, neurotransmitters, and nitrogen supply in infant-fed infants (Windmueller, 1982;Chesney et al, 1998;Agostoni et al, 2000).…”
Section: Essential Vs Nonessential Amino Acidssupporting
confidence: 77%
“…Free amino acids are constituents of the socalled nonprotein nitrogen fraction of human milk (Rudloff and Kunz, 1997;Agostoni et al, 2000). The total amount of free amino acids is around 3 mmol/l plasma with great variations (association with the nutritional behavior of the mother).…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…The total amount of free amino acids is around 3 mmol/l plasma with great variations (association with the nutritional behavior of the mother). GLU, glutamine and taurine are the prevalent amino acids accounting for around 50% of total free amino acids (Agostoni et al, 2000;Ramirez et al, 2001). Actual analyses of free GLU in milk samples of mothers delivered on time revealed 8277342 mmol/l for transitional milk and 8687462 mmol/l for mature milk (Meinardus et al, 2004;Jochum et al, 2006).…”
Section: Central Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Ingestion of small peptides has been found to appear in plasma more rapidly and uniformly as compared to free amino acids using the same amino-acid pattern (Svangerb et al, 1977). HM only contains about 5% free amino acids (Rerat, 1995) mainly as glutamic acid and taurine (Pamblanco et al, 1989;Agostini et al, 2000), and therefore departure from the HM model by adding free amino acids to formula requires careful consideration.…”
Section: Discussionmentioning
confidence: 99%